Does Regulatory Quality Matters for Stock Market Development? Evidence from Africa - Umar, Bamanga; Nayan, Sabri (International Journal of Economics and Financial Issues, 2018)
The recent global financial crisis in 2008 have awakened discussion on the necessity for wide-ranging regulations of stock markets to rescue market capitalization from further decline and restore investors' confidence . Despite efforts of previous policy reforms to sanitize the financial system and increase investment in Africa, the situation did not improve and stock markets are yet to recover from the aftershock of the crisis. This paper empirically investigates the impact of regulatory quality on African stock market development by employing pooled mean group (PMG) model for the sample period of 1996 to 2016. The findings suggest that quality regulation has a positive impact on stock market development. There is a need for far-reaching policy reforms that will ensure effective regulation of financial markets to improve market development and restore the declining investors' confidence. When strong and sound regulations of financial markets are enforced, there will be a greater expectation for the growth and development of stock market to endure the repercussion of future financial crisis. Keywords: Market Capitalization, Regulatory Quality, PMG model JEL Classifications: G12; E43; K22; O40